METRICS AND METRIC SPACES OF SOFT MULTISETS - Isah, Ahmed (FUDMA Journal of Sciences, 2023)
The theory of Soft set found applications in so many fields including multiset theory to obtain soft multisets. These theories together with some of their properties were presented. Moreover, considering the various applications of metric spaces in various fields; Metrics and metric spaces of soft multisets with some of their attributes were introduced. However, it was discovered that only pseudo-metric spaces could favorably be formulated. Moreover, soft multiset ordering was also presented.
Keywords: Metric; Multiset; Ordering; Soft multiset; Soft set